Minor psychiatric disorders in nursing: prevalence and associated factors - Evelin Daiane Gabriel Pinhatti; Renata Perfeito Ribeiro; Marcos Hirata Soares; Júlia Trevisan Martins; Maria Ribeiro Lacerda
ABSTRACT Objective: to investigate the prevalence of Minor Psychiatric Disorders and associated factors in nursing workers. Method: observational and analytical sectional study. Data were collected from 285 nursing workers. A questionnaire containing sociodemographic, occupational, psychosocial aspects of work and mental health was used. Bivariate and multivariate analysis were performed by binary logistic regression. Results: the global prevalence of suspected Minor Psychiatric Disorders among nursing workers was 32.6%. Higher prevalence rates were found among female, young, married/common-law married individuals, in the nursing assistant/technician categories, with income up to four minimum wages, developing high-demand work with low social support, high effort-reward imbalance, and over-commitment. Conclusion: the variables that remained associated with the mental health outcome in the final model were: female gender, married/common-law married, high-demand work, high effort-reward imbalance, and over-commitment.